A general purpose conceptual model for crowdsourcing projects - Assis Neto, Fábio Ribeiro de (2018)
Crowdsourcing is a method that employs people to process input data to solve a computationally complex problem, such as generating a large dataset of annotated images, audio transcriptions or video scene descriptions. In this approach, people select tasks and produce individual results according to a list of steps that leads to an efficient solution. Then, every single result must be collected, interpreted, and integrated by a platform or system supporting the crowdsourcing process. Considering that the first studies regarding this field of study were done by means of experimenting and observing platforms and systems that popularized this method. Given that, pertinent questions are: (i) besides platforms and systems, what are the essential elements that compose a crowdsourcing project?; (ii) how the humans are guided through the steps for solving the proposed problem?; (iii) how to ensure the quality of the results produced in all stages of a project?; and (iv) are there guidelines or models in the state-of-the-art to help newcomers creating their own projects? Aiming to answer these questions, a systematic literature review based on the viewpoint of individuals that seek to solve problems using the crowdsourcing method was performed during this MSc dissertation, thus stating that this domain lacks general guidelines and models that leverage the essential elements of this kind of project, as well as its relationships and descriptions. Therefore, this dissertation aims to present a set of tendencies and guidelines related to crowdsourcing project and propose a general-purpose conceptual model that represent the essential elements involved and how they relate in this kind of project, in a way that is possible to instantiate and expand this model to supply specific needs of individual projects. Furthermore, the proposed model was applied during the planning and execution stages of a crowdsourcing project designed locally.